2018
DOI: 10.1111/pedi.12753
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic associations of longitudinal adiposity in youth with type 1 diabetes

Abstract: Excess adiposity is common in youth with type 1 diabetes, yet little is known about the sociodemographic factors that predict longitudinal trajectories of body fat. We analyzed data from 363 females and 379 males with type 1 diabetes over ~9 years of follow-up (mean baseline age 12.8 ± 2.3 years in females, 13.2 ± 2.4 years in males). Estimated body fat percentage (eBFP) was calculated with validated sex- and race/ethnicity-specific equations. Group-based modeling identified three eBFP trajectories for each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…21 Another potential explanation is that vitamin D has direct effects on B-cells, such as improving insulin secretion, increasing VDR expression, and improving islet morphology. 22 The current study found a strong positive correlation between serum vitamin D and disease duration, while there was a strong negative correlation between serum vitamin D and hospital admission, FBG and HbA1c.…”
Section: Discussionsupporting
confidence: 45%
“…21 Another potential explanation is that vitamin D has direct effects on B-cells, such as improving insulin secretion, increasing VDR expression, and improving islet morphology. 22 The current study found a strong positive correlation between serum vitamin D and disease duration, while there was a strong negative correlation between serum vitamin D and hospital admission, FBG and HbA1c.…”
Section: Discussionsupporting
confidence: 45%
“…Estimated body fat percentage has been operationalized previously to examine longitudinal patterns of adiposity over time among youths with type 1 diabetes and associations of trajectory group membership with sociodemographic factors [24]. The present analysis used a longitudinal, mixed modeling approach better suited to incorporate time-varying variables that may drive change in body composition over time.…”
Section: Discussionmentioning
confidence: 99%
“…Equations are sex-and race/ethnicity-specific (white, black, Mexican-American, and "other"), and participants who identified as Hispanic/Mexican American were modeled with the Mexican American equation; all others who did not fall into one of the three specific race/ ethnicity categories were modeled with the "other" equation [23]. SEARCH previously operationalized these equations for the prediction of eBFP to examine longitudinal patterns of adiposity over time among youths with T1D [24].…”
Section: Inclusion Criteriamentioning
confidence: 99%